Visuality and virtuality : images and pictures from prehistory to perspective - Davis, Whitney (Princeton University Press, 2017)
This book builds on the theoretical framework established in Whitney Davis's acclaimed previous book, A General Theory of Visual Culture, in which he shows how certain culturally constituted aspects of artifacts and pictures are visible to informed viewers. Here, Davis uses archaeological and historical case studies to further develop his theory, presenting a new account of the interaction that occurs when a viewer looks at a picture. Davis argues that pictoriality - the depiction intended by its maker to be seen - emerges at a particular standpoint in space and time. Reconstruction of this standpoint is the first step of the art historian's craft. Because standpoints are inherently mutable and mobile, pictoriality constantly shifts in form and possible meaning. To capture this complexity, Davis develops new concepts of radical pictorial ambiguity, including "bivisibility" (the fact that pictures can always be seen in ways other than intended), pictorial naturalism, and the behavior of pictures under changing angles of view. He then applies these concepts to four cases - Paleolithic cave painting; ancient Egyptian tomb decoration; classical Greek architectural sculpture, with a focus on the Parthenon frieze; and Renaissance perspective as invented by Brunelleschi.